METODE MENAFSIRKAN KITAB SUCI MENURUT ORIGENES OBSERVASI ATAS HOMILI ORIGENES TENTANG YES 7,10-15 - Widodo, Agus (Jurnal Orientasi Baru, 2016)
Origen, in his entire life and work, was a theologian and an exegete. All of his theological thinkings are based on the Holy Scripture which he interpreted. The majority of his works as a teacher, priest, and writer were dedicated to study and interpret the Holy Scripture. Therefore, it is very appropriate to learn from him about the correct and useful methods of the interpretation of the Holy Scripture. By observing his exegesis work, the homily on Isaiah 7, 10-15, we find Origen’s six methods to interpret the Holy Scripture. By these method, Origen has instilled the very usefull method of interpreting of the Holy Scripture. Therefore, the proclamation of the Scripture increasingly enlighten and inflame the faith..